RANCANG BANGUN APLIKASI MONITORING DAN EVALUASI SISWA PADA SMPN 1 JOMBANG - Dimas Rosyid Pamungkas; Januar Wibowo; A.B. Tjandrarini (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Junior high school 1 Jombang formal educational institutions located on Jl. Taman Siswa village Pojokrejo Kesamben district, Jombang regency. Schools make school rules that contain student behavior assessments to educate student behavior better. So far, the Student section at Junior high school 1 Jombang has given part of its duties to the Counseling Guidance (BK) teacher, namely conducting inspections and recording violations due to internal factors that occur. BK teacher is a teacher who facilitates consultation with problem students. Meanwhile, any student violations either found during inspection, seen by other teachers, or originating from complaints from fellow students, students will be asked to go to the counseling teacher to record the violations committed. Every day violations at Junior high school 1 Jombang can reach approximately 23 violations, 1 student can commit 1 to 3 violations in a day. This incident can lead to miscalculating violations, and the student's points are confused, thus making the results of the evaluation inaccurate. As a result of the invalid data, the school can make inappropriate decisions that can harm students. At the time of evaluating student violations, the student section experienced difficulties including the large number of total violations committed by students in 1 semester.The website-based student violation monitoring application is the answer to the problems that student and Counseling Guidance s have, so that it can help and ease the work of Counseling Guidance and students in recording, monitoring and evaluating the violations of each student.